CUSTOMER EXPERIENCE AND TRUST TO REUSE THE “COD-CEK DULU” FEATURE: A STUDY ON SHOPEE E-COMMERCE - Zhulqurnain, Mohamad Rijal Iskandar; Raura, Anisa (Jurnal Bisnis dan Keuangan, 2025)
The Cash On Delivery (COD) feature was created to make it easier for consumers to make payments without the need for bank transfers or electronic money. However, the application of the COD payment method raises various problems in the field, not a few buyers feel that the goods they have ordered are not suitable and finally refuse to pay for the ordered goods. But currently Shopee is introducing new innovations through COD - Cek Dulu to solve the problem of the inconvenience of the previous COD payment procedure. This study aims to analyze the effect of customer experience, trust and customer satisfaction on the intention to reuse e-commerce features. This research method uses purposive sampling technique as many as 153 respondents who live in East Java, know the COD - Cek Dulu feature in the Shopee application and have made a purchase transaction at least once on the Shopee application using the COD - Cek Dulu payment method. This research data analysis uses Partial Least Square (PLS). The results of this study indicate that customer experience has a positive and significant effect on customer trust and satisfaction, trust has a positive and significant effect on customer satisfaction. Trust and customer satisfaction have a positive and significant effect on reuse intention.